Humanizing smart cities: Lisbon case study - Lourenço, B. (2022)
Smart cities are a growing phenomenon, largely driven by globalization and the digital revolution, which have enabled hyper connectivity, between people and between machines. Although there are more and more cities joining their efforts to become smart, the definition of a smart city is not consensual, there is a wide variety of definitions, which focusing on different aspects of it, cannot be considered wrong. However, it is known that a city, regardless of its intelligence, is made of people and for people, so its ultimate goal must be the constant improvement in the quality of life of its citizens. For this to happen, political power must be able to involve citizens in ongoing projects and initiatives designed to increase the city's intelligence. With this work, through the application of a questionnaire, it is intended to understand to what extent citizens are aware of the ongoing initiatives to turn Lisbon into a smart city, what is their degree of involvement during this process and what potential measures could be taken to encourage the active participation of the inhabitants in this same construction. In the end, it is expected that with the results, the Lisbon City Council, upon understanding the citizens' opinion, their perception of smart cities and the measures they think are crucial for their participation to increase, the municipality will take the measures needed to leverage the city's intelligence.